Energy Consumption, Institutional Quality and the Performance of the Manufacturing Sector in Nigeria (1999-2013) - Edame, Greg Ekpung; Okoi, Okoiarikpo Benjamin (International Journal of Energy Economics and Policy, 2015)
This study assessed the effect of energy consumption and institutional quality, on the performance of the manufacturing sector in Nigeria between 1999 and 2013 through the use of the OLS technique. The study used three measures of institutional quality: economic freedom index (ECF), corruption perception index (CPI) and contract intensive money (CIM). On the other hand, the industrial sector consumption of electricity (CSL), the total consumption of gas (GCS) and the total consumption of petroleum (PCN) were used as proxies for the consumption of energy. The results of the study show that industrial sector consumption of electricity, petroleum and gas do not have a significant impact on manufacturing sector performance. The results also indicated that the level of corruption perception has a significant effect on the performance of the manufacturing sector. Based on this, the study makes several recommendations including: the improvement in the country’s capacity to refine petroleum products; the maintenance of the current policy stand in the electricity industry by the new government; the removal of executive interference in the operations of the country’s institutions. Keywords: Energy consumption, institutional quality, ordinary least squares. JEL Classifications: E21; N60; Q14; Q20; Q40